Interrelationships among feather mercury content, body condition and feather corticosterone in a Neotropical migratory bird, the Purple Martin (Progne subis subis). (1st December 2022) - Branco, Jonathan M.; Hingst-Zaher, Erika; Jordan-Ward, Renee; Dillon, Danielle; Siegrist, Joe; Fischer, Jason D.; Schiesari, Luis; von Hippel, Frank A.; Buck, C. Loren
Abstract: Purple Martins ( Progne subis ) are migratory birds that breed in North America and overwinter and complete their molt in South America. Many of the breeding populations are declining. The eastern North American subspecies of Purple Martin ( P. subis subis ) comprises >90% of all Purple Martins. This subspecies overwinters and molts in the Amazon Basin, a region that is high in mercury (Hg) contamination, which raises the possibility that observed declines in Purple Martins could be linked to Hg exposure. Exposure to Hg results in numerous and systemic negative health outcomes, including endocrine disruption. Corticosterone (CORT) is a primary modulator of the stress and metabolic axes of vertebrates; thus, it is important in meeting metabolic and other challenges of migration. Because feathers accumulate Hg and hormones while growing, quantification of Hg and CORT in feathers provides an opportunity to retrospectively assess Hg exposure and adrenal activity of birds using minimally invasive methods. We evaluated interrelationships among concentrations of total Hg (THg) and CORT in feathers that grew in the Amazon Basin and body condition (mass, fat score) of these birds in North America. Concentrations of THg in Purple Martin feathers ranged from 1.103 to 8.740 μg/g dw, levels associated with negative physiological impacts in other avian species. Concentrations of CORT did not correlate with THg concentration at the time of feather growth. However, we found evidence that THg concentration may negatively impact the ability of Purple Martins to accumulate fat, which could impair migratory performance and survivorship due to the high energy requirements of migration. This finding suggests potential carryover effects of Hg contamination at the wintering grounds in the Amazon to the summer breeding grounds in North America. Graphical abstract: Image 1 Highlights: Up to 8.740 μg/g dw of THg found in Purple Martin feathers migrating to Amazon. THg levels found are associated with physiological impacts in other avian species. Feather THg and corticosterone levels did not correlate. Feather THg concentration correlated negatively with mass and fat score. Feathers provided suitable matrix for investigation of Hg accumulation.